A material of hierarchical interlayer-expanded MoS2 nanosheets/hollow N-doped carbon nanofibers as a promising Li+/Mg2+ co-intercalation host. Issue 19 (7th May 2021) - Yu, Xianbo; Zhao, Guangyu; Liu, Chao; Huang, Huihuang; Shen, Xiaojie; Zhang, Naiqing
Abstract : Interlayer-expanded MoS2 nanosheets/hollow N-doped carbon nanofibers were designed and exhibited superior electrochemical performances. More importantly, this electrode realizes Li + /Mg 2+ co-intercalation into the host material even at 1000 mA g −1 . Abstract : Combining the high operational security of magnesium-ion batteries (MIBs) and the fast Li intercalation mechanism of lithium-ion batteries (LIBs), Li + /Mg 2+ hybrid-ion batteries (LMIBs) have been developed and are regarded as a promising source of stored power for applications. However, pristine MoS2 with an interplanar distance of 0.62 nm only allows Li + intercalation, leading to limited energy densities and mediocre electrochemical performance. Herein, we designed and prepared a material consisting of hierarchical interlayer-expanded MoS2 nanosheets/hollow N-doped carbon nanofibers (O–MoS2 /HN-CNFs) with interplanar expanded O–MoS2 (0.94 nm). HN-CNFs adequately conduct electrons, and the expanded interlayer spacing of O–MoS2 ensures that Mg 2+ and Li + simultaneously intercalate into the host, even at 1000 mA g −1 . Additionally, O–MoS2 /HN-CNFs can significantly reduce the ion diffusion barrier and increase the number of intercalated active sites. As a result, O–MoS2 /HN-CNFs exhibited superior rate capabilities, good cycling performance, and long-term cycling stability, with a reversible capacity of 134.4 mA h g −1 at 1000 mA g −1 after 2000 cycles.